Pengaruh Sleep Hygiene terhadap Kualitas Tidur Lansia dengan Insomnia: The Effect of Sleep Hygiene on Sleep Quality in Elderly with Insomnia - Fiktina Vifri Ismiriyam; Wulansari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2025)
The elderly are an age group that is very susceptible to insomnia. A Javanese proverb says that the elderly will